Pemilu.AI sebagai Inovasi Demokrasi Digital: Analisis E-Governance dalam Pemilu Indonesia - Farsya Ellysya; Nur Azizah Hikmatulloh; Zafirah Irdina Mulyana; Fatkhuri Fatkhuri; Maisarah Mitra Adrian (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The development of Artificial Intelligence (AI) has transformed digital democracy practices and technology-based governance (e-governance), including the implementation of elections in Indonesia. This study aims to analyze the utilization of Pemilu.AI as a digital democracy innovation and its influence on transparency, public participation, and electoral accountability within the perspective of e-governance. This research employed a qualitative approach using a descriptive-analytical method through document analysis of scientific journals, digital publications, online news, and information available on the Pemilu.AI platform. Data were analyzed using thematic analysis to identify patterns and meanings related to the use of AI in digital democracy. The findings indicate that Pemilu.AI contributes to improving access to political information in a faster, more interactive, and accessible manner. The platform also supports public information transparency and expands public participation in the digital democratic sphere. However, the implementation of AI in digital elections still faces several challenges, including low digital literacy, potential algorithmic bias, the spread of disinformation, and the lack of comprehensive regulations governing AI in political spaces. Therefore, stronger regulations and improved digital literacy are necessary to ensure that the use of AI in elections remains transparent, accountable, and democratic.